Interaction, Diffusion, and Fertility Transition in Costa Rica: Quantitative and Qualitative Evidence - Rosero Bixby, Luis (1999)
This chapter examines the role played by diffusion through social interaction in the Costa Rican fertility transition. The literature about the causes of fertility transition has traditionally focused on the socio-economic and cultural determinants of the motivation for having large or small families. To a somewhat lesser degree, it has also considered supply factors limiting or facilitating access to contraception, that is, the role of family planning programmes. The concern here is with the third type of causal agent of fertility transition, that is, the autonomous spread, or contagiousness, of fertility control. If Costa Rican data support the proposition that social contagion processes shaped fertility decline, then an empirical foundation exists for Simmons's claim that 'programmes may generate their own demand through diffusion from early users to others'.